Halal Medicine in Indonesia: Navigating Sharia and State Law - Surur, Achmad Tubagus; Adinugraha, Hendri Hermawan; Sain, Zohaib Hassan (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This research examines halal medicine in Indonesia from the perspectives of Sharia disputes and state law. This research method has involved qualitative, legal analysis, and field observation. The multidisciplinary approach and triangulation of methods have provided in-depth and valid insights into the complex issue of halal medicine, encompassing Sharia disputes and state law. This research’s findings suggest that research on halal medicine in Indonesia is urgent, considering the issue’s importance from a religious, legal, economic, and public health perspective. In-depth and comprehensive research can help resolve disputes between Sharia principles and state law, increase consumer awareness and trust, and encourage the development of a competitive and innovative pharmaceutical industry. This research concludes an urgent need to bridge the gap between Sharia principles and state law in Indonesia’s halal medicine. Synchronization of state law and Sharia principles in halal pharmaceutical practices in Indonesia is achieved through regulations such as Law No. 33/2014 on Halal Product Guarantee, certification by BPJPH and MUI, public education, and industry innovation, ensuring Sharia compliance without compromising public health. Indonesia can strengthen its position as a leader in the halal pharmaceutical industry while ensuring that public health interests and Sharia compliance can coexist with a more integrated approach, more effective regulations, and increased public awareness.